194k views
11 votes
Please help 10 points

Please help 10 points-example-1

1 Answer

5 votes

Answer:

The value of x is -2 and 2.

Explanation:

When solve an expression, you have to make the expression equals to 0 by moving all the terms to one side :

x² - 3x - 1 = -3x + 3

x² - 3x - 1 + 3x - 3 = 0

x² - 4 = 0

Next, you have to factorize and solve it :

x² - 4 = 0

x² + 2x - 2x - 4 = 0

x(x + 2) - 2(x + 2) = 0

(x + 2)(x - 2) = 0

x + 2 = 0

x = -2

x - 2 = 0

x = 2

User Colin Dumitru
by
4.7k points